A matched cohort study of convalescent plasma therapy for COVID‐19. Issue 4 (22nd February 2021) - Sostin, Oleg V.; Rajapakse, Pramuditha; Cruser, Brigid; Wakefield, Dorothy; Cruser, Daniel; Petrini, Joann
Abstract: Introduction: COVID‐19, caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is a public health crisis. Prior studies demonstrated successful use of convalescent plasma therapy for treatment of other viral illnesses. Our primary objective was to evaluate treatment efficacy of convalescent plasma in patients with COVID‐19. Materials and Methods: In this retrospective matched cohort study, we enrolled recipients of convalescent plasma collected from donors recovered from laboratory‐confirmed SARS‐CoV‐2 infection under the single patient eIND process. We individually matched 35 cases with 61 controls based on age, gender, supplemental oxygen requirements, and C‐reactive protein level at the time of hospital admission. We compared the outcomes of in‐hospital mortality and hospital length of stay between the groups. Results: In‐hospital mortality was 20% among the cases and 24.6% among the controls ( P  = .61). A multivariable logistic regression model that included age, gender, duration of symptoms, need for mechanical ventilation, and pharmacologic interventions revealed no significant difference in mortality by study group ( P  = .71). The median length of stay was significantly greater among convalescent plasma recipients compared with controls, 10 (IQR, 6‐17) vs 7 (IQR, 4‐11) days, P  < .01. The difference was not significant after controlling for covariates ( P  > .1). Conclusions: We did not find convalescent plasma reduced in‐hospital mortality in our sample, nor did it reduce length of stay. Further investigation is warranted to determine the efficacy of this treatment in patients with COVID‐19, particularly early in the disease process.